Phytochemical Analysis and In Vitro Cytotoxicity of n-Hexane Extract of Kaempferia pandurata and its Nanoparticle to Breast Cancer MCF-7 Cells - Fadilah Fadilah (Journal of Global Pharma Technology, 2019)
Background: Finger root (Kaempferia pandurata) is a medicinal herb which has shown anticancer activity as potential targeted-therapy towards estrogen receptor positive breast cancer. Objective: This research was conducted to analyze the phytochemical contents of n-hexane extract of Kaempferia pandurata and its nanoparticle to the growth of estrogen positive breast cancer MCF-7 cells. Methods: Kaempferia pandurata rhizome was extracted in n-hexane, and its phytochemical contents was analyzed by simple phytochemical test and thin layer chromatography. Nanoparticle was then synthesized from n-hexane extract of Kaempferia pandurata. Finally, the n-hexane extract of Kaempferia pandurata and its nanoparticle were then tested using MTT Assay to MCF-7 cells in order to determine their inhibition rate and IC50. Results:. The extraction of Kaempferia pandurata rhizome in n-hexane extract was conducted successfully. Through simple phytochemical testing, n-hexane extract of Kaempferia pandurata contained flavonoids, triterpenoids, and tannins. Thin layer chromatography using non-polar eluent (n-hexane : ethyl acetate = 5 :1) showed eight spots with Rf values of 0,12; 0,18; 0,23; 0,29; 0,41; 0,55; 0,62; 0,80. MTT assay resulted in IC50 value of 94.387 ± 11.667 μg/mL and 31,298 ± 0,242 μg/mL for n-hexane extract of Kaempferia pandurata and its nanoparticle respectively. Discussion: The phytochemical contents of n-hexane extract of Kaempferia pandurata (flavonoid, triterpenoid, tannin) was shown to have anticancer activities on breast cancer cells n-hexane extract of Kaempferia pandurata and its nanoparticle has moderately active anticancer activities towards estrogen positive breast cancer MCF-7 cells. Nanoparticle enhances n-hexane extract of Kaempferia pandurata’s entry to cancer cells. Conclusion: N-hexane extract of Kaempferia pandurata and its nanoparticle can be a potenial anticancer agent towards estrogen positive breast cancer.